A REFLECTIVE LOOK AT THE USE OF GAMES IN MATHEMATICS TEACHING - Francisco da Silva Coelho, Acássio (Journal of Interdisciplinary Debates, 2022)
Elementary education is a starting point in the teaching and learning process, this school initiation must have practices and resources that dynamize the assimilation of knowledge in the classroom. So, this research is born from the perspective that the use of mathematical games in the teaching of mathematics has gained emphasis in the school environment as a result of the contribution to the student’s cognitive development. The present research sought to present a methodological proposal based on mathematical games in order to create dynamic strategies for the teaching and learning process related to the teaching of mathematics. To support this bibliographic research, we relied on works dealing with mathematics and mathematical games. It is expected to present the importance of bringing games to the classroom, not as a proposal just to amuse students, but to make them acquire the mathematical knowledge presented under a new approach. Therefore, games show good results in terms of expanding student learning through alternative problem-solving methods, encouraging the ability to create and participate more actively in math classes.